PROFESSIONAL ETHICS OF PUBLIC ELEMENTARY SCHOOL TEACHERS IN JAKARTA PROVINCE, INDONESIA - Ahmad Rustam; Wathroh Mursyidi; Muhammad Zhilal; Eva dwi kumala sari; Rika Sa’diyah (FORUM PAEDAGOGIK, 2022)
ABSTRACTThe purpose of this research is to analyze the professional ethics of public elementary school teachers in Jakarta Province, in Indonesia. This is a descriptive research with data collected through questionnaires by asking the respondents to fill in several statements related to teacher professional ethics. The distributed questionnaires contain statements on the professional ethics of teachers in schools from September 2018 to February 2019. Furthermore, the cluster random sampling process was used to obtain data from 437 teachers in 34 public elementary schools located in the four administrative cities of Jakarta (East Jakarta, West Jakarta, North Jakarta, and South Jakarta) in accordance with the State Civil Apparatus. The analytical method used in this research is a descriptive-exploratory analysis where the data obtained is analyzed and interpreted, therefore, reflective conclusions can be drawn. The validity of the instruments used was validated using the second-order Confirmatory Factor Analysis (CFA) with the help of M-Plus software. The analysis results show that the professional ethics of Public Elementary School teachers in Jakarta Province is 64.1% and categorized as good.Â